Islamic Bank Merger and the Efficiency–Risk Trade-off: Evidence from Bank Syariah Indonesia - Royani Anwari (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
The merger of three state-owned Islamic banks into PT Bank Syariah Indonesia Tbk (BSI) in 2021 marked a major structural shift aimed at strengthening efficiency and competitiveness within Indonesia’s Islamic banking industry. This study examines the dual impact of the merger, focusing on the trade-off between efficiency gains and credit risk within the Maqasid al-Shariah framework, particularly the principle of hifz al-mal (protection of wealth). A quantitative panel data approach is employed, utilizing a Fixed Effects model on four major Islamic banks over the 2018–2024 period. To address pre-merger data limitations, a synthetic data construction technique is used for the 2018–2020 period. The merger’s impact is assessed through the Hifz al-Mal Performance Index, a composite indicator capturing both asset development and asset protection dimensions. The findings reveal a dual pattern: profitability (ROA) and operational efficiency (BOPO) improved following the merger, while credit risk increased, as indicated by higher Non-Performing Financing (NPF). The regression results show a positive but marginally significant effect of the merger (β₁ = 7.452; p = 0.057). Sensitivity analysis further demonstrates that this positive effect depends on the index weighting scheme, with results becoming statistically insignificant when greater emphasis is placed on asset protection. These findings highlight the importance of balancing tanmiyat al-mal (wealth development) with the safeguarding function of hifz, particularly in the context of large-scale corporate restructuring in Islamic banking. ABSTRAK - Merger Bank Syariah dan Trade-off antara Efisiensi dan Risiko: Bukti dari Bank Syariah Indonesia. Merger tiga bank syariah BUMN menjadi PT Bank Syariah Indonesia Tbk (BSI) pada tahun 2021 menjadi tonggak penting dalam upaya meningkatkan efisiensi dan daya saing industri perbankan syariah di Indonesia. Penelitian ini mengkaji dampak ganda dari merger tersebut dengan menelaah keseimbangan antara peningkatan efisiensi dan risiko kredit dalam kerangka Maqasid al-Shariah, khususnya prinsip hifz al-mal (perlindungan harta). Penelitian ini menggunakan pendekatan kuantitatif dengan desain data panel melalui model Fixed Effects pada empat bank syariah utama selama periode 2018–2024. Untuk mengatasi keterbatasan data sebelum merger, digunakan teknik konstruksi data sintetis pada periode 2018–2020. Dampak merger diukur melalui Indeks Kinerja Hifz al-Mal, yaitu indeks komposit yang mencerminkan dimensi pengembangan dan perlindungan harta. Hasil penelitian menunjukkan pola yang bersifat ganda: terjadi peningkatan profitabilitas (ROA) dan efisiensi operasional (penurunan BOPO), namun diiringi peningkatan risiko kredit yang tercermin dari kenaikan Non-Performing Financing (NPF). Secara agregat, hasil regresi menunjukkan pengaruh positif yang signifikan secara marginal (β₁ = 7.452; p = 0.057). Uji sensitivitas mengungkap bahwa hasil tersebut sangat bergantung pada skema pembobotan indeks, di mana pengaruh merger menjadi tidak signifikan ketika bobot perlindungan aset ditingkatkan. Temuan ini menegaskan pentingnya menjaga keseimbangan antara tanmiyat al-mal (pengembangan harta) dan fungsi perlindungan (hifz) dalam konteks restrukturisasi perbankan syariah.